A Systematic Review of the Role of Human Resource Management in Enhancing Time and Cost Efficiency in Steel Structure Projects - FA. Luky Primantari; Silvia Yulita Ratih Setyo Rahayu; Zandra Dwanita Widodo (International Journal of Industrial Innovation and Mechanical Engineering, 2025)
Steel structure projects are increasingly favored in the construction industry due to their benefits in execution time efficiency and long-term cost savings. However, the suboptimal management of human resources (HRM) remains a significant challenge in achieving these efficiencies. This study aims to systematically review the role of HRM in enhancing time and cost efficiency in steel structure projects. A Systematic Literature Review (SLR) was conducted based on the PRISMA protocol, analyzing 35 accredited scientific articles published between 2013 and 2023. The articles were sourced from national databases such as Garuda and Neliti, and data were extracted using standardized documentation instruments. The analysis reveals that workforce planning, project-based training, performance monitoring, and inter-team coordination are key managerial aspects that consistently contribute to improving both time and cost efficiency. Visualization of topic networks using VOSviewer highlights strong interconnections between themes such as "training," "schedule control," and "performance evaluation," all of which are critical components of strategic HRM practices. This study concludes that HRM plays a crucial role in achieving efficiency in steel structure projects, especially through the integration of technical workflows and managerial control systems. Effective workforce planning ensures that the right skills are available at the right time, while performance monitoring and training programs help enhance productivity and reduce delays. The findings suggest the necessity for formulating HR policies that are based on workload analysis and the improvement of real-time workforce evaluation mechanisms. Furthermore, the study calls for further research to test integrative models for HRM practices in steel-based construction projects in Indonesia. This research opens avenues for refining HRM strategies to support the construction industry’s efficiency goals, offering insights for future studies and practical applications in the field.